FORMULASI DAN UJI FISIK SEDIAAN SALEP EKSTRAK DAUN JAMBU AIR (Syzygium aqueum (Burm F.) Alston) DENGAN VARIASI TIPE BASIS SALEP - Yunita Dian Permatasari; Nava Kirani; Umi Nafisah; Aptika Oktaviana Trisna Dewi (Jurnal Farmasindo, 2020)
Water guava leaves contain chemical compounds such as flavonoids, tannins and saponins. As a medicinal preparation, water guava leaves can be made into an ointment. This study aims to determine the ointment formulation, conduct physical evaluation of the ointment and determine the effect of different types of ointment base extracts of water guava leaves on physical properties. Water guava leaves extract was made by maceration method of ethanol 70% solvent. Ointment are made with four types of bases which include hydrocarbon base, absorption, water washed and water soluble. Each formula was tested for physical properties including organoleptic, homogeneity, pH, dispersal, and adhesion. The data obtained were then analyzed using the One Way ANOVA test method. The results showed that the four ointment formulas had different shapes and colors, had the same odor and had good homogeneity. The pH test of the hydrocarbon bases ointment was 4.09, the absorption bases was 3.98, the water-washed bases was 4.33, and the water-soluble base was 3.87 did not meet the pH test parameters. The dispersibility test results for hydrocarbon bases 6.20 cm, absorption basis 6.19 cm met the test parameters, base ointment was washed with water 3.99 cm, water soluble base 3.49 cm did not meet the dispersibility test parameters. The results of the adhesion test for hydrocarbon bases 11.85, absorption bases 12.11, water washable bases 20.03, and water soluble bases 4.97, which means they meet the adhesion test parameters. The results of the One Way ANOVA test showed that the pH test, spreadability and adhesion had the same significant value, namely 0.000 <0.05. These results indicate that the different types of ointment bases used have a significant effect on pH, dispersion and adhesion.